Розробка цифрового ультразвукового канального вимірювача потоку повітря та температури - Дерев’янко, Є. А.; Кримовський, Р. С. (My University, 2018)
In this study, an ultrasonic airflow measuring device has been developed. Airflow within rooms, important for environmental control in high-performing buildings and in labs, hospitals, and data centers, is currently almost never monitored because of the expense, power draw, directional sensitivity, and fragility of existing airspeed sensors. The result is that existing building control systems cannot predict energy flows accurately.
Keywords: Ультразвуковий канальний вимірювач; повітря та температура